Metodika práce s třídním kolektivem v inkluzivní třídě se zaměřením na žáky s narušenou komunikační schopností Metodická příručka - Chleboradová, Barbora (Masaryk University Press, 2020)
Title in English: Methodology of working with inclusive class collective with focus on pupils with impaired communication ability. The theoretical part describes the bases for the communication process and its disruption in a broader context, focusing on school age and reflection in the current and educational communication situation. The research part offers the results of the survey, which results from long-term cooperation with two primary schools of inclusive type, in which pupils with different forms of special educational needs are educated. In these schools, precisely, in these classrooms in which pupils with impaired communication ability were educated, the activities aimed at strengthening communicative competence and social ties were carried out at regular intervals during one school year.